Ruang dan Identitas Sosial: Reproduksi Identitas Kelas Menengah Muslim di Pesantren Ar Risalah Padang - Tyka Rahman (Jurnal Sosiologi Andalas, 2023)
This study discusses the reproduction of the social identity of the Muslim middle class through space; boarding school. Data were collected using interviews and observations. This study departs from the argument that the Indonesian Muslim middle class and the middle class in general have different characteristics. The findings of this study are that Islamic boarding schools have an influence on the social, political, and religious views of the middle class. Even the Muslim middle class has different religious practices and different socio-political views. This makes the face of the Indonesian middle class very diverse. The Indonesian middle class generally expresses their urban side closely with an educated urban life. The middle class presents themselves with local, urban and global values. Middle class identity is formed with values ​​oriented to religious-nationalism values.